2001
DOI: 10.1007/s002670010240
|View full text |Cite
|
Sign up to set email alerts
|

Public and Occupational Risks of the Nevada (USA) Test Site

Abstract: The Nevada Test Site (NTS), north of Las Vegas, was the scene of hundreds of nuclear weapons tests over four decades, both above- and below ground. There is considerable interest, both in neighboring communities and elsewhere, in the risks it poses. Overall, the greatest risks are nonradioactive in origin, with occupational risks to employees and accident risks in transporting low-level nuclear wastes to the NTS from other Department of Energy (DOE) sites ranking highest. For radiation risks, that to workers h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Public spending of US$1100 million leads to loss of 1100/70 ∼ 15 lives lost according to Viscusi 258 and to 1100/7 ∼ 150 lives lost according to Lutter and Morrall. 257 An additional study 260 concluded that the price tag of radiation protection is about 5000 times higher than that of protection of workers from all other (and more probable) events. It can be therefore said that per each statistical life saved by nuclear regulation (if LNT is valid), there are 15 to 5000 “statistical murders” (the term used by Graham).…”
Section: Discussionmentioning
confidence: 99%
“…Public spending of US$1100 million leads to loss of 1100/70 ∼ 15 lives lost according to Viscusi 258 and to 1100/7 ∼ 150 lives lost according to Lutter and Morrall. 257 An additional study 260 concluded that the price tag of radiation protection is about 5000 times higher than that of protection of workers from all other (and more probable) events. It can be therefore said that per each statistical life saved by nuclear regulation (if LNT is valid), there are 15 to 5000 “statistical murders” (the term used by Graham).…”
Section: Discussionmentioning
confidence: 99%
“…Another study concluded that costs of radiation protection are about 5000 times higher than the cost of protection of workers from all other and much more probable events (Inhaber 2001). • At Chernobyl and Fukushima, compulsory relocation (ordered by the authorities on the basis of ICRP recommendations which are based on the LNT model predictions) led to social destruction, which caused significant emotional/psychological problems and life-shortening.…”
mentioning
confidence: 97%
“…• According to the researchers from the Harvard School of Public Health (Graham 1995), spending $100,000,000 per year on controlling radiation emissions might save 1 life-year per year, if the LNT model were valid, while life-saving medical program median cost is $19,000 per lifeyear saved. Another study concluded that costs of radiation protection are about 5000 times higher than the cost of protection of workers from all other and much more probable events (Inhaber 2001). • At Chernobyl and Fukushima, compulsory relocation (ordered by the authorities on the basis of ICRP recommendations which are based on the LNT model predictions) led to social destruction, which caused significant emotional/psychological problems and life-shortening.…”
mentioning
confidence: 99%
“…Because of long half-life and high radiotoxicity of 239 Pu, its mobility is a key concern involved in both performance assessments of high-level radioactive waste repositories12 and remediation of contaminated fields such as nuclear test sites34. Transport velocity of Pu ( U Pu ) is one necessary parameter for both evaluating its mobility and then predicting its potential risks to human health.…”
mentioning
confidence: 99%